If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 6) = 42 Reorder the terms: (6 + 2x) = 42 Remove parenthesis around (6 + 2x) 6 + 2x = 42 Solving 6 + 2x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2x = 42 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 42 + -6 2x = 42 + -6 Combine like terms: 42 + -6 = 36 2x = 36 Divide each side by '2'. x = 18 Simplifying x = 18
| (6x^3-6x^2+2x)+(8x^3+9x^2-13x)= | | -5+4(2x+13)=16 | | 24+1.50m=3m | | 18x^2+9xy-20y^2=0 | | -9y-12=8-4y | | 3x+4=6x-8 | | 4x+7(-x+4)=13 | | 8-(3n-1)=5-4n | | (2r+6)/5=-4 | | y^3-7y^2+3y-21=0 | | 8=30 | | 2x-10=4x+30 | | 3x+5-7(x+1)=4x+3 | | 7h-4=12-3h | | -64=4x-2(-5x-10) | | (m-2)/9=3 | | -5v-10=-110 | | 1+8e-2e=22 | | 3=-1.5n | | 16d^2-14d-15=0 | | 2(6-x)=2x+6 | | 4(x)+10=38 | | 21-4h-13=37+13h | | 2x-6=6x-18 | | 2x-6(3x+2)=180 | | (t+8)/4=6 | | 8+4m=9m+-7 | | t/6=12 | | 7x-5-2x+10=90 | | -2x-3(-x+13)=-33 | | 6b-7=-139 | | 5x-6-x=4+x+5 |